Ethics - The other name for good governance - Sekhar, R.C. (1998)
Following an exploration of concepts of ethics and good governance and their interrelationship, the author examines how emphasis on ethics can facilitate realisation of good governance. He relates the discussion to the nature of State and bureaucracy in the ethical web of mutual expectations and attaining administration's objectives of optimum control with the least transaction cost. He then raises several issues having a bearing on realising good governance. - Reproduced
Keywords: Ethics; Public administration; Good governance